Enhancing MSMEs Performance through Halal Compliance, Community Networks, and Social Media Optimization: Evidence from Depok, Sleman, Yogyakarta - Mei Maemunah; Angistya Pinakesti; Clarissa Zahra Prasiwi; Eny Nurnilawati (Widya Dharma Journal of Business - WIJoB, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute a vital backbone of the local economy in Sleman Regency, especially in the Depok Sub-district. Nevertheless, ensuring business sustainability remains a significant challenge, particularly in the face of intensifying market competition and the introduction of new regulations, such as the phased implementation of mandatory halal certification beginning in October 2024. This research seeks to examine strategies for sustaining MSMEs by integrating three key elements: adherence to halal certification standards, strengthening solidarity within MSMEs forums, and leveraging social media as an effective marketing instrument. Employing a qualitative method with a case study design, the study focuses on capturing the lived experiences of MSMEs actors in Kapanewon Depok. Data collection will involve in-depth interviews, participant observation, and document analysis. The findings are anticipated to shed light on the interaction dynamics among these three pillars and to generate practical recommendations for MSMEs practitioners, local authorities, and relevant stakeholders in formulating more impactful empowerment initiatives. Ultimately, the study aims to support the development of resilient and competitive MSMEs in the digital era.